Gold ore identification in Santa Catarina Gabbro using electrical resistivity tomography (ERT) and visualization of mineralization in three dimensions, São Sepé, Rio Grande do Sul, Brazil - Lenhare, Bruno Daniel [UNESP] (2023)
This work presents the geological-geophysical characterization of a probable occurrence of gold in Santa Catarina Gabbro, in Sao Sepe region, Rio Grande do Sul state, southern Brazil. Previous works have indicated the presence of gold in the region in current sediments geochemical prospecting campaigns and suggests that the source area would be the Santa Catarina Gabbro. To investigate over this probable occurrence of gold, geological and structural surveys were conducted, followed by the acquisition of geophysical information using the DC-resistivity and IP methods, with the dipole-dipole array. The geophysical data were processed in 2D inversion and then interpolated to allow the three-dimensional visualization of possible mineralization. Interpretations based on the compilation of geological and geophysical data, in association with the regional structural context, suggest that the probable mineralization were originated from the intrusion of the Sao Sepe Granite, whose hydrothermal fluids were hosted in fractures during the tectonic events that occurred in the region. The results obtained in this work allow to outline a feasible deposit architecture with the geological context of the region and to assist a future drilling strategy aimed at the identified probable targets.